Formulation and In vitro Interaction of Rhodamine-B Loaded PLGA Nanoparticles with Cardiac Myocytes - Jonderian, Antranik; Maalouf, Rita (Frontiers in Pharmacology, 2016)
This study aims to characterize rhodamine B (Rh B) loaded poly(D,L-lactide-co-glycolide; PLGA) nanoparticles (NPs) and their interactions with cardiac myocytes. PLGA NPs were formulated using single emulsion solvent evaporation technique. The influence of varying parameters such as the stabilizer concentration, the sonication time, and the organic to aqueous ratio were investigated. The diameter, the dispersity, the encapsulation efficiency and the zeta potential of the optimized NPs were about 184 nm, 0.19, 40% and -21.7 mV, respectively. In vitro release showed that 29% of the Rh B was released within the first 8 h. Scanning electron microscopy measurements performed on the optimized NPs showed smooth surface and spherical shapes. No significant cytotoxic or apoptotic effects were observed on cardiac myocytes after 24 and 48 h of exposure with concentrations up to 200 μg/mL. The kinetic of the intracellular uptake was confirmed by confocal microscopy and cells took up PLGA NPs within the 1st hours. Interestingly, our data show an increase in the NPs’ uptake with time of exposure. Taken together, we demonstrate for the first time that the designed NPs can be used as potential probes for drug delivery in cardiac myocytes.